Analisis Pengaruh Nilai Pelanggan, Destination Image, dan Kualitas Pelayanan terhadap Minat Kunjung Ulang Wisatawan dengan Kepuasan Pengunjung sebagai Variabel Intervening (Studi Kasus pada Obyek Wisata Bukit Cinta Rawa Pening Kabupaten Semarang) - Mulyana, Andika Pratama; Sutopo, Sutopo (Diponegoro Journal of Management, 2019)
The purpose of this research is to analyze some factors which affect of TouristStatification and Revisiting Interest as Customer Value, Destination Image,and ServiceQuality. This study uses primer data from tourist visiting The Bukit Cinta RawaPeningtourism object located in Semarang Regenc. The sampling method usedPurposive Sampling. Data analysis used a regression analysis tool was used using theSPSS 23.0 program tool. The results of test found that is a positive and partiallysignificant influence between the value of customers on interest in revisiting; andbetween customer value and visitor satisfaction; and also between visitor satisfactionwith interest in tourist revisits. But there is a positive influence that is not partiallysignificant between destination image and the quality of service to interest in repeatvisits; also between destination image and service quality to visitor satisfaction.